The Achaean Federal Cult Part 1: Pseudo-Julian, Letters 198 - Spawforth, Antony (Tyndale bulletin, 1995)
This paper explores the evolution of emperor-worship at Corinth in the first century A.D. Specifically, it argues that a Greek ‘letter’ in the correspondence on the emperor Julian should be redated to c. A.D. 80-120 and identified as a petition from the city of Argos to the Roman governor of Achaia, in which the Argives sought exemption from payments towards the cost of celebrations of the imperial cult at the Roman colony of Corinth. Since these celebrations involved many of the province’s cities, the paper goes on to argue that they can be identified with the collective cult—its place of celebration previously uncertain— known from inscriptions to have been founded by the member-cities of the Achaean league in the mid-first century A.D.